Southwest train robberies: hijacking the tracks along the Southern Corridor - Hocking, Doug (TwoDot, 2023)
"Southwest Train Robberies: Hijacking the Tracks along the Southern Corridor chronicles the train heists throughout Arizona and New Mexico at the turn of the twentieth century, and the robbers who pulled off these train jobs with daring, deceit, and plain dumb luck! Many of these blundering outlaws escaped capture by baffling law enforcement"-- Provided by publisher